Understanding teachers’ experiences of work in marketised contexts: a scale construction approach - Winchip, Emily Joy (2019)
The aim of this research was to study the experiences of teachers working in marketised contexts to understand the effect on their work. For-profit education management organisations are increasing their involvement in all facets of education and the influences of marketisation may be particularly evident in the growing sector of international schools. The problem addressed in this research is the difficulty understanding the experiences of teachers in marketised contexts. This may be especially difficult as teachers’ perceptions are unheard when market-based reforms are assumed to solve all issues.